Nicotine replacement therapy as a smoking cessation aid among disadvantaged smokers: What answers do we need?. (14th December 2015) - Paul, Christine; Wolfenden, Luke; Tzelepis, Flora; Yoong, Serene; Bowman, Jenny; Wye, Paula; Sherwood, Emma; Rose, Shiho; Wiggers, John
Abstract: In Australia and New Zealand, population groups who experience social disadvantage smoke at much higher rates than the general population. As there are limited data specific to these groups regarding the success of nicotine replacement therapy for smoking cessation, this commentary will provide an overview of the relevant international literature supplemented with observational data relevant to the policy contexts in Australia and New Zealand. [Paul C, Wolfenden L, Tzelepis F, Yoong S, Bowman J, Wye P, Sherwood E, Rose S, Wiggers J. Nicotine replacement therapy as a smoking cessation aid among disadvantaged smokers: What answers do we need? Drug Alcohol Rev 2016;35:785–789]